Bawaslu Electoral Oversight in Peripheral Malinau Local Election 2024: Pengawasan Bawaslu dalam Pilkada Periferal Kabupaten Malinau 2024 - Christian Roten Gidion; Yulianto Yulianto; Sofjan Aripin (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Regional elections as a manifestation of popular sovereignty require credible oversight mechanisms to safeguard democratic procedures at the local level. Specific Background: In Indonesia, the Elections Supervisory Agency plays a strategic role in supervising electoral stages, particularly in regions with geographical constraints and distinct socio-political characteristics such as border and peripheral areas. Knowledge Gap: Existing studies predominantly emphasize national or urban electoral contexts, leaving limited scholarly attention to supervisory practices in peripheral regions with restricted infrastructure and strong patron–client relations. Aims: This study examines how electoral oversight was conducted by the Malinau Regency Elections Supervisory Agency during the 2024 local election and identifies contextual factors shaping supervisory practices in a peripheral setting. Results: The findings indicate that oversight activities were carried out across all electoral stages through participatory supervision, early identification of administrative violations, media monitoring, and the use of simple information technologies. However, supervisory practices were constrained by limited human resources and budget, uneven geographical access, weak inter-institutional coordination, low public legal awareness, and challenges related to civil servant neutrality. Novelty: This study integrates geographical border conditions, local socio-political relations, and institutional capacity limitations into the analysis of electoral oversight, extending prevailing theoretical discussions that are largely urban-oriented. Implications: The results suggest that electoral oversight in peripheral regions requires adaptive and context-sensitive strategies that align regulatory frameworks with local institutional capacity and community participation to support procedural compliance and democratic integrity. Highlights • Electoral oversight in Malinau was conducted across all Pilkada stages through participatory and media-based monitoring• Geographic constraints and limited institutional resources shaped supervisory practices in border areas• Local socio-political relations influenced community participation in reporting electoral violations Keywords Electoral Oversight; Bawaslu Supervision; Local Democracy; Peripheral Regions; Malinau Regency